Pluriatividade e sua influência sobre o emprego da agricultura familiar na região nordeste do Brasil - Pádua, Daniela Sousa Lopes de (2023)
The present work aims to investigate the influence of pluriactivity on the level of occupation of family farming in the municipalities of Northeast Brazil. Given the benefits of pluriactivity attested by the literature, the working hypothesis is that pluriactivity raises the level of employment in family farming. Studies related to this topic are important, as family farming is the main source of labor within the rural sector in Brazil, being responsible for a large portion of food production in the country. The empirical strategy consists of using an unconditional quantile regression (URQ) model to capture any non-linear effects of pluriactivity on the level of employment in family farming. The sample consists of the 2017 Agricultural Census data for the Northeast region. As a proxy for pluriactivity, we use the Shannon diversity index for temporary and permanent crops and non-agricultural activities. Our results show evidence that an increase in pluriactivity (agricultural and non-agricultural activities) generates a positive effect on average employment in family farming, especially in regions with a low family employment level. In municipalities with a high level of family employment, the effect of pluriactivity is exhausted. In this sense, the importance of public policies that promote pluriactivity in rural areas, particularly in locations with low occupation in family farming, is desired.